Analysis of Prices of Patented Medicines Listed In The National Formulary and E-Catalogue In Pusat Jantung Nasional (RSPJN) Harapan Kita Hospital, â€œDharmaisâ€ Cancer Hospital, and Pusat Otak Nasional Hospital (RSPON), Jakarta Province - Sari Mutiarani; Prih Sarnianto; Erna Kristin (Syntax Literate, 2022)
Cost control of drugs plays an important role in the implementation of the Health Insurance Program and one of the efforts related to this is the through the drug selection process in National Formulary (Fornas) and the determination of drug prices in e-catalogue to obtain drugs, especially patented drugs, at affordable prices without reducing the quality of health service. This study aims to analyze the decline in drug prices during the patent period that listed in Fornas and e-catalogue and the savings in drugs costs during the patent period at the hospital and the factors that influence the decline in drug prices. In this descriptive study, secondary data was taken crosswise from the information management system in three special hospitals in Jakarta - RSPJN Harapan Kita, "Dharmais" Cancer Hospital and RSPON- which listed in Fornas and used during January 2019 - June 2020, and drug price list according to the e-Catalogue and the regular in that period. The results showed a decrease in the price drugs that were still in patent period when they were listed in Fornas and e-Catalogue compared to the price of regular market by 55,1%. The Price rediction that occurred has resulted in savings in drug costs during the patent period at RSPJN Harapan Kita by 47,2%, RSPON (55,3%) and the â€œDharmaisâ€ Cancer Hospita (36,1%). Drug tax value, NIE publication year, and type of drug therapy class that tend to cause drug prices to fall higher in addition to the impact of the implementation of Fornas in RSPON, RSPJN Harapan Kita, and "Dharmais" Cancer Hospital.